An association of VNTR polymorphism in intron3 of IL-4 gene with susceptibility to typhoid fever in Khartoum State, Sudan - Manal A. Fadl; Mawada A. Aydarous; Canguan Mao; Afshan Yasmeen (Kuwait Journal of Science)
Host genetic factors play a role in determining susceptibility to infectious diseases ofhumans. Polymorphisms in Interleukin 4 (IL-4), an anti-inflammatory cytokine thatregulates the balance between T helper (Th1) and Th2 immune responses, has beenreported to affect the risk of infectious and autoimmune diseases. In this study we aimed to investigate the possible association of variable numberof tandem repeat (VNTR) polymorphism in intron3 of IL-4 with susceptibility totyphoid fever in Sudanese patients. We analyzed the 70 bp intron-3 VNTR repeatpolymorphism in 200 DNA samples obtained from patients with blood cultureconfirmedtyphoid fever and 200 samples from randomly selected healthy controlsfrom the same city area. The intronic VNTR polymorphism was genotyped using PCR,followed by agarose gel elec trophoresis. The result showed that the genotypes of thetarget VNTR polymorphism in both cases and controls were not deviated from Hardy-Weinberg equilibrium (X 2, df=3=6.468, P˃ 0.05 and X 2, df=1=0.07, P˃ 0.5 respectively).The observed difference of the R3R3 & R2R2 genotypes among cases and controls isnot statistically significant (P= 0.09 and P=0.46 respectively). However, a significantincrease in the 2R3R genotype frequency among cases compared to the controls wasobserved (P˂0.05), indicating that the heterozygote 2R3R of VNTR polymorphism ofIL4 might affect individual susceptibility to typhoid fever in our population.